2018
DOI: 10.3390/rs10122000
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution UAV-Based Hyperspectral Imagery for LAI and Chlorophyll Estimations from Wheat for Yield Prediction

Abstract: The efficient use of nitrogen fertilizer is a crucial problem in modern agriculture. Fertilization has to be minimized to reduce environmental impacts but done so optimally without negatively affecting yield. In June 2017, a controlled experiment with eight different nitrogen treatments was applied to winter wheat plants and investigated with the UAV-based hyperspectral pushbroom camera Resonon Pika-L (400-1000 nm). The system, in combination with an accurate inertial measurement unit (IMU) and precise gimbal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 46 publications
1
60
1
Order By: Relevance
“…Previous research has revealed significant differences in the results of UAV RS-based crop growth monitoring due to the use of different sensors [14]. With the exception of a few studies using Lidar [52] and non-imaging active or passive canopy sensors [7,53], most of the UAV-based studies have used imaging spectrometers or multispectral [16,48] and hyperspectral cameras [19]. However, professional imaging sensors, UAV systems, and their supporting software may lead to a high total cost for ordinary consumers and cause challenges for technical promotion.…”
Section: Potential Of Consumer-grade Uav-based Digital Imagery For Crmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has revealed significant differences in the results of UAV RS-based crop growth monitoring due to the use of different sensors [14]. With the exception of a few studies using Lidar [52] and non-imaging active or passive canopy sensors [7,53], most of the UAV-based studies have used imaging spectrometers or multispectral [16,48] and hyperspectral cameras [19]. However, professional imaging sensors, UAV systems, and their supporting software may lead to a high total cost for ordinary consumers and cause challenges for technical promotion.…”
Section: Potential Of Consumer-grade Uav-based Digital Imagery For Crmentioning
confidence: 99%
“…Considering remotely sensed variables, traditional spectral indices such as VIs or CIs have been widely used in UAV RS-based crop biomass estimation [57], flower count [58], vegetation detection [59], yield prediction [19,48], and other applications of precision agriculture [60]. On the other hand, other studies have also used spatial information derived from UAV-based imagery, such as digital crop surface models (CSMs) [36], degree of canopy cover [61], plant height [36], and textures [49] for crop growth monitoring.…”
Section: Potential Of Consumer-grade Uav-based Digital Imagery For Crmentioning
confidence: 99%
See 1 more Smart Citation
“…Before discussing different GAI-models or possible areas of application, it is necessary to consider the applicability of the Sequoia camera. Other studies using different UAV-based sensors in general (Duan et al, 2017;Zhou et al, 2017;Condorelli et al, 2018;Kanning et al, 2018), predecessors of the Sequoia sensor (Verger et al, 2014;Haghighattalab et al, 2016;Nebiker et al, 2016) and in particular the Sequoia sensor (Condorelli et al, 2018;Tunca et al, 2018) showed promising results in terms of comparability with ground-based multispectral sensors and their implication to generate information about crop characteristics. Our results match to these findings; the Sequoia camera provides reliable and sufficiently accurate data for crop monitoring purposes on plot level in terms of a scientific context.…”
Section: Discussionmentioning
confidence: 99%
“…The Sentinel-2 multispectral instrument includes three bands in the red-edge region centered at 705, 740, and 775 nm, which were found to be of great interest for crop monitoring [46]. Unmanned aerial vehicle (UAV) platforms coupled with imaging sensors are able to collect multispectral or hyperspectral imagery and offer great possibilities in the precision farming [47,48]. When using these remote sensing techniques to investigate peanut canopy information, the spectral information collected by the sensors may not only come from the adaxial leaf surfaces but also the abaxial leaf surfaces.…”
Section: Discussionmentioning
confidence: 99%